(untitled) (Journal of Maternal and Child Health, 2019)
Background: Preeclampsia is a major cause of maternal morbidity and mortality that occurs at gestational age >20 weeks. It is characterized by hypertension and proteinuria. Shortly, severe preeclampsia may develop into eclampsia accompanied by seizures or coma. This study aimed to examine the determinants of severe preeclampsia in Surakarta, Central Java. Subjects and Method: This was a case-control study conducted in Gajahan health center, Dr. Moewardi hospital, and Surakarta hospital, Surakarta, Central Java, from October 2018 to December 2018. A sample of 200 pregnant women was selected by fixed disease sampling. The dependent variable was severe preeclampsia. The independent variables were age, education, stress, parity, history of hypertension, history of diabetes mellitus (DM), ANC visit, and family history of hypertension. Data on preeclampsia were obtained from medical record. The other data were collected by questionnaire. The data were analyzed by path analysis. Results: Severe preeclampsia was directly and positively associated with age <20 or ?35 years (b= 1.23; 95% CI= 0.31 to 2.14; p= 0.008), history of hypertension (b= 1.54; 95% CI= 0.58 to 2.51; p= 0.002), history of DM (b= 1.12; 95% CI= 0.21 to 2.03; p= 0.016), and stress (b= 1.58; 95% CI = 0.60 to 2.56; p = 0.002). It was negatively associated with parity (b= -0.96; 95% CI= -1.90 to - 0.01; p = 0.046) and ANC visit (b= - 1.98; 95% CI= -2.91 to - 1.05; p<0.001). Severe preeclampsia was indirectly associated with education, ANC visit, and family history of hypertension. Conclusion: Severe preeclampsia is directly and positively associated with age, history of hypertension, history of DM, and stress. It is negatively associated with parity and ANC visit. Severe preeclampsia is indirectly associated with education, ANC visit, and family history of hypertension. Keywords: severe preeclampsia, determinants, path analysis Correspondence: